Pool of items to measure Primary Health Care workers' knowledge on healthy eating - Lígia Cardoso dos Reis; Patricia Constante Jaime (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE To develop and validate a self-applicable instrument for measuring primary health care (PHC) workers' knowledge on healthy eating. METHODS A six-step methodological study to develop and validate a measurement instrument: item development based on the Brazilian Dietary Guidelines' chapters; content validation with a panel of experts; face validation with potential instrument users; online instrument reevaluation by participants of the content and face validation panels; online application of the instrument with PHC workers; confirmatory factor analysis for construct validation. RESULTS A first version with 25 items underwent content and semantic changes in the content and face validation panels, being reorganized into a second version with 22 items. In the reevaluation, participants considered 21 questions to be clear and representative of the Brazilian Dietary Guidelines, with one being excluded. This third version of the instrument underwent confirmatory factor analysis after being applied online with 209 PHC workers from all Brazilian macroregions. We excluded five items in this analysis: four due to bivariate empty cells and one due to low discrimination capacity. The final model, with 16 items loaded onto one dimension, returned good fit indices [χ2(104) = 119.047, p = 0.1486; RMSEA = 0.026 (90% CI = 0.000 to 0.046), Cfit = 0.979; CFI = 0.924; TLI = 0.913]; its information peak was below average. CONCLUSIONS The instrument proved to be valid and accurate for assessing PHC workers with below average knowledge of the Brazilian Dietary Guidelines. It might contribute to improving actions to promote healthy eating in Brazilian PHC settings by identifying the need for training health professionals.